Ownership Structure and Environmental Disclosure among Nigerian Listed Firms - Musa, Haruna Muhammed (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
The study investigated the effect of ownership settings on Nigerian listed firms’ environmental disclosure for the period 2012 – 2022. The predicting variables includes managerial ownership, foreign ownership, government ownership, and institutional ownership. A correlational approach was adopted to explore the variables’ natural relationships. Published annual reports of 95 Nigerian listed firms were used as a source of secondary data. The extent of environmental disclosure by the sampled firms was measured using the Global Reporting Index (GRI). Panel regression analysis revealed that foreign, government and institutional ownership have a significantly positive effect on environmental disclosure among Nigerian listed firms. Although, the findings did not yield conclusive evidence on a link between managerial ownership and environmental disclosure among the companies. The results of this study are crucial for regulatory authorities, stakeholders and policymakers, as it pinpoint the most effective strategies for firms to address environmental disclosure challenges and highlight key factors that drive and enhance environmental transparency. As a result, the study recommended that the industry regulators should work together with government in revitalizing the nation’s economy which in turn encourage more investment from foreign investors. Additionally, management should prioritize and encourage government and institutional holding in the Nigerian listed firms as there monitoring characteristics can enhance firm's environmental disclosure practices.
Keywords: Environmental Disclosure; Managerial Ownership; Foreign Ownership; Government Ownership; Institutional Ownership